Kosmopolitanisme Kehidupan Intelektual di Ḥijāz sebelum Wahabisme, Studi Kasus Sintesis Teologi Asya’ri-Akbari oleh Ibrāhim al-Kurānī (w. 1690 M) - M. Khoirul Huda (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2025)
The study of Islam in the archipelago cannot be separated from the intellectual dynamics in Ḥijāz. This is as shown by the study of Bruinessen, Azra, and Fathurrahman. On the other hand, very few have commented on the condition of Ḥijāz in the 16th to 19th centuries. The book  Intellectual Life in the  Ḥijāz before Wahhabism Ibrāhīm al-Kūrānī's (d. 1101/1690) Theology of Sufism by Naser Dumairieh tries to fill the gap. Using tsabat books, books that contain scientific sanad that connect with the authors of classical works, Dumairieh explores the circulation of knowledge, figures and works in the region. He found that the circulation of  science in Ḥijāz was so intensive that it succeeded in giving  birth to dynamics that influenced other regions in the Islamic world, especially Southeast Asia. The intellectuals of Ḥijāz, represented by the figure of Ibrāhīm al-Kūrānī valued the transmissive (manqūl) and rational (ma'qūl) sciences. The result of this scientific dynamic is the success of synthesizing theology and Sufism within the framework of the Ash'ari-Akbari fusion. This synthesis view was accepted by students from Southeast Asia such as Abdurrauf al-Singkilī and Yūsuf al-Makassarī. The intellectual dynamics of 16th-century Ḥijāz show that the Islamic world of the post-classical period cannot be categorized as an era of regression.